Impacts of climate change and the end of deforestation on land use in the Brazilian legal amazon - Lapola, David Montenegro; Schaldach, Ruediger; Alcamo, Joseph; Bondeau, Alberte; Msangi, Siwa; Priess, Joerg A.; Silvestrini, Rafaella; Soares-Filho, Britaldo Silveira (American Meteorological Society, 2011)
Climate change scenarios vary considerably over the Amazon region, with an extreme scenario projecting a dangerous (from the human perspective) increase of 3.8°C in temperature and 30% reduction in precipitation by 2050. The impacts of such climate change on Amazonian land-use dynamics, agricultural production, and deforestation rates are still to be determined. In this study, the authors make a first attempt to assess these impacts through a systemic approach, using a spatially explicit modeling framework to project crop yield and land-use/land-cover changes in the Brazilian Amazon by 2050. The results show that, without any adaptation, climate change may exert a critical impact on the yields of crops commonly cultivated in the Amazon (e.g., soybean yields are reduced by 44% in the worst-case scenario). Therefore, following baseline projections on crop and livestock production, a scenario of severe regional climate change would cause